Permainan Rakyat dan Olahraga Tradisional Gantao Sebagai Ekspresi Kegiatan Kebudayaan Masyarakat Bima - Irfan, Irfan; Amar, Khairul; Faidin, Nahrul; Bahri, Samsul (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Devotion regarding the traditional sports game Gantao is one of the traditional game cultures of the Bima people which has an aesthetic value of movements using bare hands, which is played by 2 warriors to carry out dexterous movements to attack each other. which was accompanied by several strains of traditional Bima music. The problem with the traditional sport of gantao is that people have never received socialization about gantao, and studios rarely participate in performance activities to strengthen socialization. The method is 1). Educational methods, 2). Performance method, 3). Evaluation methods, 4). Sustainability method. The results of cultural activities are performances of folk games and the traditional sport of Gantao as cultural expressions. This activity is carried out based on the spirit of promoting traditional sports. Performance activities can motivate cultural preservation through government policies, budget support, and facilitation for studios. Apart from that, teachers are also motivated to implement the gantao game in schools. The impact on society of this activity can form the value of preserving the game of gantao as one of the activities carried out in their lives. The impact on students of the gantao activity is to gain knowledge about the traditional sports game gantao and implement it in the school environment as the formation of disciplined, independent, responsible, and improved physical health.